Point of Sale Display of Plain Cigarette Packages : Finger prints of the industry - AY, NADİYE PINAR (My University, 2021)
Objective: Tobacco industry has been using the point of sales (POS) as a promotion outlet for their products. Previously, in Istanbul, the complience with the advertising ban has been found to be low. This study aims to investigate the effect of plaing packaging implementation on the compliance of the POS in 2020. Method: This observational study was carried out at the six trade-dense districts of Istanbul by using the "Framework Convention Alliance Shadow Reporting" Methodology in 2020. All the POS in 1 km diameter were visited. A form is filled about the display format and photos were taken. Results: Of the 177 POS visited ; at 100 % the display was at the eye-level of children, at 97 % the shelves contained tobacco advertising, at 92% the tobacco products were visible from outside the shop, at 85 % the stacking of the packs were against the legislation, at 80 % tax stamps were covering the pictorial warnings, at 73 % the display shelves were donations of the tobacco companies, at 52 % the pictorial warning were invisible due to perpendicular placement, at 31 % the shop sign indicated a tobacco brand. The same violation strategy was recorded in 93% of the sale points throughout various districts. A stacking design with various pack sizes was noted in all shops. Measurements and Main Results: A consistent pattern of stacking that made the pictorial warning invisible was noted in the majority of the POS in various districts of the city, indicating orchestrated industry interference. The findings of this study implies that plain packaging renders pictorial warnings prominent. The displays at POS must be made visible to the eye of the consumers by preventing industry interference.
Keywords: Tıp; Sağlık Bilimleri; Dahili Tıp Bilimleri; Göğüs Hastalıkları ve Allerji; Medicine; Health Sciences; Internal Medicine Sciences; Chest Diseases and Allergy; SOLUNUM SİSTEMİ; Klinik Tıp; Klinik Tıp (MED); RESPIRATORY SYSTEM; CLINICAL MEDICINE; Clinical Medicine (MED); Solunum Bakımı; Akciğer ve Solunum Tıbbı; Respiratory Care; Pulmonary and Respiratory Medicine; Education; Smoking; Health policy